Surface relief gratings formed by microphase-separated disperse red 1 acrylate-containing diblock copolymers. (14th February 2018) - Spiridon, Mitica Cezar; Aissou, Karim; Mumtaz, Muhammad; Brochon, Cyril; Cloutet, Eric; Fleury, Guillaume; Hadziioannou, Georges
Abstract: Sinusoidal surface-relief gratings (SRGs) formed by microphase separated photoresponsive poly(dimethylsiloxane)- block -poly(methyl acrylate- co -disperse red 1 acrylate) (PDMS- b -P(MA- co -DR1A)) chains are investigated. Different PDMS- b -P(MA- co -DR1A) were prepared by a multi-step synthetic approach which overcomes the challenges inherent to the synthesis of well-defined PDMS-based block copolymers (BCPs) having a DR1A dye content up to 50 wt%. A sinusoidal SRG (amplitude ≈ 5 nm, wavenumber ≈ 315 nm) interferometrically inscribed onto a thin PDMS- b -P(MA- co -DR1A) layer exhibiting an out-of-plane cylindrical structure with a period of ∼34 nm is demonstrated. Such kind of "two-colored" multiscale patterned surfaces could be envisioned as guiding patterns to efficiently direct the self-assembly of a BCP upper-layer via a hybrid chemo-/grapho-epitaxial alignment of BCP features. Graphical abstract: Image 1 Highlights: A multistep synthetic approach leads to block copolymers bearing azobenzene moieties. Block copolymer thin films exhibiting different morphologies were produced. "Two-colored" multiscale patterned surfaces were obtained through SRG inscription.